2021
DOI: 10.15388/ekon.2021.100.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Innovation and Technology after COVID-19: a few Directions for Policy Makers and Regulators in the View of Old and New Disruptors

Abstract: Innovation and technology have led to the redefinition of business models and development of new ones in many bricks and mortar sectors.  Similarly, blockchain and fintech have impacted the finance and banking industries and are expected to further affect them in the future, leading some media to coin the expression “Uberization of banking”.  The authors extrapolate from sharing economy models to conclude that while blockchain and fintech are poised to advance finance and banking, there are no disruptive featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study by Pompella and Constantino (2021) confirmed that FinTechs showed a significant degree of resilience during the global pandemic. This finding was also confirmed by the World Bank study (2021) which showed on a sample of 1,385 fintech companies from 169 countries that FinTechs recorded a strong year-over-year growth in the first half of 2020.…”
Section: Impact Of the Pandemic On Fintech Companies And Financial In...mentioning
confidence: 90%
“…A study by Pompella and Constantino (2021) confirmed that FinTechs showed a significant degree of resilience during the global pandemic. This finding was also confirmed by the World Bank study (2021) which showed on a sample of 1,385 fintech companies from 169 countries that FinTechs recorded a strong year-over-year growth in the first half of 2020.…”
Section: Impact Of the Pandemic On Fintech Companies And Financial In...mentioning
confidence: 90%
“…The level of financial innovation also needs to be regulated because it can trigger economic movements and at the same time trigger economic instability (Lauretta, 2018). Regulation can have a positive or negative effect depending on how strong the strategy is and how clear and binding the policies created by the local government are (Kok Pompella & Costantino, 2021;Katusiime, 2021). For example, macroeconomic policy has a positive effect in the short term but has a negative effect in the long term Katusiime, 2021).…”
Section: What Are the Antecedents Of Financial Innovation?mentioning
confidence: 99%